Visible‐light‐responsive antibacterial activity of Au‐incorporated TiO2 layers formed on Ti–(0–10)at%Au alloys by air oxidation. Issue 5 (19th February 2019) - Ueda, Takatoshi; Ueda, Kyosuke; Ito, Koyu; Ogasawara, Kouetsu; Kanetaka, Hiroyasu; Mokudai, Takayuki; Niwano, Yoshimi; Narushima, Takayuki
Abstract: Rutile TiO2 layers were formed on substrates of Ti–(0–10)at%Au alloys by a simple process of air oxidation, and their antibacterial activities were evaluated under visible‐light irradiation ( λ ≥ 400 nm). Au was introduced into the TiO2 layers on Ti–(1–10)at%Au alloys and existed as both metallic Au nanoparticles and dissolved Au 3+ ions. The TiO2 layers that formed on Ti–5at%Au and Ti–10at%Au alloys exhibited visible‐light photocatalytic activity, that is, degradation of stearic acid and antibacterial activity against Escherichia coli . These visible‐light activities were attributed to the surface plasmon resonance of metallic Au nanoparticles and the decrease in bandgap energy caused by dissolved Au 3+ ions. The formation of hydroxyl radicals observed under visible‐light irradiation is attributable to antibacterial activity. From a cost perspective, a Ti–5at%Au alloy is more suitable as a substrate for the formation of a TiO2 layer with antibacterial properties than a Ti–10at%Au alloy. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 991–1000, 2019.